Endoscopic transnasal approach for removing pituitary tumors - Mirian Cabral Moreira de Castro; Luciane Maria Pereira Michel; Mariana Moreira de Castro Denaro; Pollyana Anício Magalhaes Gontijo; Atos Alves de Sousa (Arquivos de Neuro-Psiquiatria)
To describe a series of 129 consecutive patients submitted to the resection of pituitary tumors using the endoscopic transsphenoidal approach in a public medical center. Method: Retrospective analysis based on the records of patients submitted to the resection of a pituitary tumor through the endoscopic transsphenoidal approach between 2004 and 2009. Results: One hundred and twenty-nine records were analyzed. The tumor was non-secreting in 96 (74.42%) and secreting in 33 patients (22.58%). Out of the secretory tumors, the most prevalent was the growth hormone producer (7.65%), followed by the prolactinoma, (6.98%). Eleven patients developed cerebral spinal fluid (CSF) fistulas, and four of them developed meningitis. One patient died due to intracerebral hemorrhage in the postoperative period. Conclusion: The endoscopic transsphenoidal approach to sellar tumors proved to be safe when the majority of the tumors were non-secreting. The most frequent complication was CSF. This technique can be done even in a public hospital with financial limits, since the health professionals are integrated.